2008
DOI: 10.1088/1468-6996/9/2/024408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clays on the fire-retardant properties of a polyethylenic copolymer containing intumescent formulation

Abstract: Organophilic clay particles were added to a standard intumescent formulation and, since the role of clay expansion or intercalation is still a matter of much controversy, several clays with varying degrees of interlayer distances were evaluated. The composites were obtained by blending the nanostructured clay and the intumescent system with a polyethylenic copolymer. The flame-retardant properties of the materials were evaluated by the limiting oxygen index (LOI), the UL-94 rating and thermogravimetric analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
6
13
0
Order By: Relevance
“…Obviously, the addition of carbon nanofibers greatly shortens time to ignition of GR-CNF, which agrees well with reported data [1][2][3][4][5][6][7][8][9]. Among different explanations, Kashiwagi et al believed that carbon nanotubes and polymer resin have different absorption characteristics of the external emission [1].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Obviously, the addition of carbon nanofibers greatly shortens time to ignition of GR-CNF, which agrees well with reported data [1][2][3][4][5][6][7][8][9]. Among different explanations, Kashiwagi et al believed that carbon nanotubes and polymer resin have different absorption characteristics of the external emission [1].…”
Section: Resultssupporting
confidence: 86%
“…These nanoparticles are environmentally friendly and will not produce toxic gases. Layered silicates are widely used for an improvement in flame retardancy, but carbon nanotubes (CNTs) have been proved more efficient [1][2][3][4][5][6][7][8][9]. It has been found [1][2][3][4] that their flame retarding performance can be achieved through the formation of a relatively uniform network of carbon nanotubes, covering the entire sample surface without any cracks or gaps.…”
Section: Introductionmentioning
confidence: 99%
“…2e). Specifically, CC showed a higher weight percent of carbon and a lower weight percent of sodium, both relative to UC, thus confirming the modification with the organic modifier [58]. After thermal degradation however, the weight percent of carbon decreased significantly for CC900, while the weight percent of magnesium, aluminum, and silicon increased; further, no sodium was observed.…”
Section: Resultsmentioning
confidence: 55%
“…Previous studies carried by our group, FLUMAT (Laboratory of Fluids and Materials), showed the synergistic action of montmorillonite on the performance of intumescent systems containing APP (Exolit 422) and PER, revealing that the montmorillonite d‐ spacing has a strong influence on the synergistic effect. The results showed that the increase in the d‐ spacing to values higher than 35 Å reduces the flame retardant properties of the studied composites (Ribeiro, Estevão, & Nascimento, ; Ribeiro, Estevão, Pereira, & Nascimento, ).…”
Section: Introductionmentioning
confidence: 99%